Comportamiento de la mortalidad por VIH/Sida en Colombia durante los años 2015 al 2020 (2023)
To describe the behavior of HIV/AIDS mortality in Colombia during the years 2015 to 2020, taking into account sociodemographic variables such as sex, age, social security, marital status, educational level and department of death and residence, by calculating crude and adjusted rates